Immediate Ocular Changes After Light-Emitting Diode Displays Exposure—A Preliminary Study - Lin, Chia-Chen; Hung, Jia-Horung; Huang, Yi-Hsun (Frontiers in Medicine, 2022)
Purpose: Computer vision syndrome (CVS) is one of the most frequently encountered problems among video display terminals (VDT) users, but little is known regarding the short-term effect after exposure to light-emitting diodes (LED). The purpose of this study was to determine if short-term exposure to LED leads to changes in corrected distance visual acuity (CDVA), lipid layer thickness (LLT), blink rates, partial blink ratio, and computer vision syndrome questionnaire (CVS-Q) score. Design: Prospective, cross-sectional study. Methods: In this study, participants were recruited at the National Cheng-Kung University Hospital, a tertiary referral center in southern Taiwan, for examination. Participants were asked to complete the CVS-Q and undergo a series of ocular examinations, including CDVA, LLT, blink rates and partial blink ratio before and after watching an LED display for 15 minutes. Main Outcome Measures were changes in CDVA, LLT, blink rates, partial blink ratio, and CVS-Q measurements. Results: In total, 120 eyes from 60 participants (mean age: 35.7 ± 9.4 years) were included; 31 participants were men (51.7 %), and 29 were women (48.3 %). The CDVA, LLT, blink rates, and partial blink ratio did not change after watching the LED display. The CVS-Q score significantly improved after short-term LED exposure (P <0.001). A subgroup analysis of subjects with a baseline LLT of <60 nm or ≥60 nm determined that LLT significantly decreased in individuals with a baseline LLT of ≥60 nm (P = 0.016). Conclusion: Short-term use of LED displays reduced LLT in individuals with a baseline LLT of ≥60 nm, despite the visual symptoms of CVS improved subjectively. Therefore, digital device users should be aware of the potential negative effects of LED exposure on the eyes.